Pengaruh motivasi kerja, lingkungan kerja, dan Kepercayaan diri terhadap kepuasan kerja karyawan PT. Radio Mayangkara Ria Kota Blitar - Mohammad, Zaidan Rafif; Santoso, Bowo (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The goals of an organization are realized by paying attention to human resources (HR). In addition, the work environment, motivation, job satisfaction, and trust from employees also play a role. PT. Radio Mayangkara Ria Blitar is the chosen location of the research which aims to obtain an analysis of work motivation, work environment/place, and self-confidence, whether there is an effect on the employees of PT. Radio Mayangkara Ria Blitar who experienced job satisfaction. In addition, Saturated sampling was chosen as the method in the study. Secondary and primary data is used where primary data is in the form of questionnaire results for 33 employees of PT. Radio Mayangkara Ria. Partial Least Square (PLS) is used by researchers to analyze. The research shows that employee job satisfaction is positively and significantly influenced by motivation and work environment. However, self-confidence has a negative and insignificant effect on employees at PT. Radio Mayangkara Ria whether you experience job satisfaction.